Hadis-Hadis âMisoginisâ Dalam Persepsi Ulama Perempuan Kota Banjarmasin - Dzikri Nirwan, Saifuddin Fatrawati Kumari (IAIN Antasari Banjarmasin, 2013)
The current trends in South Kalimantan has indicated that women moeslem scholars start to emerge from many religious gathering. Their roles as preacher cannot be neglected. This fact, furthermore, is representated in the form of their comprehension to their religion main guidanceâQurâan and Hadith. From the context of Hadith, the comprehension of women moeslem scholars on the notion that tends to degrade women becomes significant to be investigated through interview and documentation technique, the writer utilizes descriptive method and fiqh al-hadist approach. It is found that the perceptions of women moeslem scholars to the misogynistic Hadith have a similarity that is, not looking these Hadiths as having misogynistic connotations. Among 7 sampels of the scholars being investigated, only one scholar has the impression of âharsâ and dictatorâ from the Hadith. However, the scholar only dares to say âimpressionâ, not the actual fact from the Hadith. Since it is only an impression, the scholar tries to seek for another meaning to delete the impression. The assumption of the respondents from the hadith is much influenced by their perspectives that strongly hold âtraditionalâ values. The traditional values usually look the relationships between men and women hierarchically, that is placing one higher that the other.